Konseling Art dengan Media Gambar untuk Meningkatkan Self Disclosure Mahasiswa - Karyanti Karyanti (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
University students need to express themselves in making friend relationship with other university students. Self-disclosure is an act to tell about the private self-condition to the other university students voluntarily. University students’ self-disclosure can reduce the anxiety felt by themselves when they are making friend relationship with other university students. The anxiety experienced by the university students in making friend relationship can make them become difficult to express their opinions, feelings, and they will not share any information with other university students. The university students who are difficult to express themselves will experience uncomfortable conditions and tends to be avoided by the other university students. The focus of the university students’ self-disclosure to other university students is an intervention or special counseling strategies offered. By hoping that when the counseling strategy can be implemented, it can overcome the problems of less harmonious friendship between the university students. Counseling strategy that offered to the university students’ self-disclosure is a self-disclosure training by using art counseling with pictures media.